A new freshwater snail genus and species (Gastropoda: Caenogastropoda, Cochliopidae) with extremely spinous shells from sub-recent spring deposits in northeastern Mexico - Czaja, Alexander; Covich, Alan P.; Neubauer, Thomas A.; Estrada-Rodríguez, José Luis; Ávila-Rodríguez, Verónica; Mata, Jorge Sáenz (Zootaxa, 2022)
A new monotypic genus of freshwater snail from late Holocene spring deposits in Viesca, Coahuila (Mexico), is described based on shell morphology. Spinopyrgus luismaedai n. gen. et n. sp. has two to three carinate shells with long and wide shovel-shaped spines, strong axial ridges and a pointed protoconch. All sculptural ornamentations on the teleoconch are part of the calcareous shell material and not projections of the periostracum. This combination of shell features and their almost “marine-like” appearance is unknown among North American recent and fossil freshwater snails. Because of its shell characteristics, we placed the new genus tentatively in the Cochliopidae. The springs of Viesca dried up in the second half of the 20th century so that any living occurrence of this species in neighboring areas is unlikely, rendering the new genus and species possibly extinct.